(untitled) (Texas Journal of Philology, Culture and History, 2023)
The article summarizes the experience of testing various methods of mnemonics in the classroom with children of primary school age who have learning difficulties. An analysis is made of the principles, methods and techniques of mnemonics, as well as forms of work with children’s parents. The ways of compiling and memorizing developing mnemonic tables are considered